Caregiver profiles and determinants of caregiving burden in Ghana - Sanuade, O.A.; Boatemaa, S. (Public health, 2015)
Due to the growing elderly population, the high cost of care in Ghana and low coverage of the National Health Insurance Scheme, demands for family caregiving have become more imperative in Ghana than ever before. Many caregivers experience high burdens, yet literature on caregiving in Ghana is lacking. This study examined caregiver profiles and determinants of the burden of caregiving in Ghana. Cross-sectional study. This study used data from Wave 1 of the World Health Organization (WHO) Study on Global Ageing and Adult Health (2007-2008). In total, 238 caregivers were analysed in the study. The burden of caregiving was measured using the WHO Impact of Caregiving Scale. Independent sample t-tests, correlations and analysis of variance were used to investigate associations between background characteristics and the burden of caregiving. Linear regression was used to examine determinants of the burden of caregiving. The mean age of caregivers was 61 years (standard deviation 14.5), and the male:female ratio was approximately equal. On average, approximately two adults per household required care. Less than five percent of caregivers received financial, emotional, health, physical and personal care support. Place of residence, provision of financial, health and physical support to care recipients, and receipt of financial, physical and health support were significant determinants of the burden of caregiving. This study found a mismatch between the number of people needing care and the number of people providing care. In order to improve the health of caregivers and care recipients, there is a need to provide financial support for caregivers. In addition, pro-caregiving government programmes and policies should be established. Copyright © 2015 The Royal Society for Public Health. Published by Elsevier Ltd. All rights reserved. Caregiver profiles and determinants of caregiving burden in Ghana | Request PDF. Available from: https://www.researchgate.net/publication/279300335_Caregiver_profiles_and_determinants_of_caregiving_burden_in_Ghana [accessed Sep 14 2018].
Keywords: Caregiving burden; Determinants; Types of support received; Ghana